Respuesta :

The formula for midpoint is

([tex]\frac{x_{1}+x_{2}}{2}[/tex], [tex]\frac{y_{1}+y_{2}}{2}[/tex])

Essentially you are taking the mean of the end points

27.

In this case:

[tex]x_{1} =0\\x_{2} =4\\y_{1} =1\\y_{2} =1[/tex]

^^^Plug in these number into the formula given above...

([tex]\frac{0+4}{2}[/tex], [tex]\frac{1+1}{2}[/tex])

([tex]\frac{4}{2}[/tex], [tex]\frac{2}{2}[/tex])

Simplify the fractions:

(2, 1)

^^^This is the coordinate of the midpoint

28.

In this case:

[tex]x_{1} =-3\\x_{2} =-3\\y_{1} =4\\y_{2} =-4[/tex]

^^^Plug in these number into the formula given above...

([tex]\frac{-3 + (-3)}{2}[/tex], [tex]\frac{4+(-4)}{2}[/tex])

([tex]\frac{-6}{2}[/tex], [tex]\frac{0}{2}[/tex])

Simplify the fractions:

(-3, 0)

^^^This is the coordinate of the midpoint

Hope this helped!

~Just a girl in love with Shawn Mendes

Answer:

27)  (2,1)

28)  (-3,0)

Step-by-step explanation:

To find the midpoint, you average your x's to get the x-coordinate and you average your y's to get the y-coordinate.

On number 27:

The x's are 0 and 4. The average of 0 and 4 is (0+4)/2 = 4/2 = 2.

The y's are 1 and 1. The average of 1 and 1 is (1+1)/2  =  2/2   =1.

The midpoint for number 27 is (2,1).

On number 28:

The x's are -3 and -3. The average of -3 and -3 is (-3+(-3))/2  =-6/2 = -3.

The y's are 4 and -4.  The average of 4 and -4 is (4+(-4))/2  =0/2   =0.

The midpoint for number 28 is (-3,0).